Development and Validation of Azari Version of Speech Recognitifon Threshold Test in Adult Azari Population and Compiling Psychometrically Equivalent Lists - Asma Hammami Dizaj; Nariman Rahbar; Behrooz Mahmoodi-Bakhtiari; Seyyed Jalal Sameni; Nayiere Mansouri (Auditory and Vestibular Research)
Background and Aim: One of the various measures used in speech audiometry is the speech recognition threshold. The aim of this study is to construct psychometrically equivalent lists containing Azari two-syllable words to evaluate speech reception threshold in Azari-speaking adults. Methods: This study is a cross-sectional comparative study of test construction. Common two-syllable words were collected from Azari books. Words with features of ease, familiarity, and relatedness as well as phonetic balance and phonetic dissimilarity were included in 5 lists of 10 words. The lists were evaluated for psychometric evaluations and validity and reliability on young Azari population at 5 intensity levels from –5 to 15 dB HL. After two to four weeks, people were tested again under the same conditions. Results: All 5 lists showed favorable face, content validity index and content validity ratio. The average speech thresholds obtained were 9.62, 9.77, 9.57, 9.67 and 9.57, respectively. Cronbach’s alpha coefficient and halving were obtained above 0.8 in all 5 lists. Test-retest reliability was also significant (p<0.001). Conclusion: The review and analysis performed on the data show that all 5 lists have psychometric homogeneity and alignment and show a high degree of validity and reliability; which makes them suitable for evaluating speech reception threshold in hearing centers of Azari regions.